2013
DOI: 10.1063/1.4790277
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molybdenum doping on the switching characteristic in silicon oxide-based resistive switching memory

Abstract: This report compares Mo-doped and undoped SiO2 thin films of a similar thickness as well as MoOx. The Mo-doped SiO2 film exhibited switching behavior after the forming process, unlike the undoped SiO2 film. Through material analyses, a self-assembled layer is observed in the Mo-doped SiO2 film. Due to the formation of this layer, the thickness required to be broken down is effectively reduced. Subsequently, the occurrence of the switching behavior in the thinner SiO2 film further confirmed the supposition. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, nonlinear I-V characteristic appears at higher electric field in HRS. The classical nonlinear conduction mechanisms, including Schottky emission, 19 Poole-Frenkel emission, 20 and space charge limited current (SCLC), 21,22 were all adopted to try to fit the nonlinearity of the measured I-V relation, and it was found that SCLC has the best fit. At low voltages (<0.32 V), I-V curve exhibits linear behavior and the conduction behavior is governed by ohmic law.…”
mentioning
confidence: 99%
“…However, nonlinear I-V characteristic appears at higher electric field in HRS. The classical nonlinear conduction mechanisms, including Schottky emission, 19 Poole-Frenkel emission, 20 and space charge limited current (SCLC), 21,22 were all adopted to try to fit the nonlinearity of the measured I-V relation, and it was found that SCLC has the best fit. At low voltages (<0.32 V), I-V curve exhibits linear behavior and the conduction behavior is governed by ohmic law.…”
mentioning
confidence: 99%
“…3(c) and 3(d). The on/off ratio of the device is slightly lower than those reported in the literature, 13 but it can be improved by increasing the number of oxygen vacancies using oxygen doping, for example, as reported in Ref. 14.…”
mentioning
confidence: 88%
“…Apart from changes in the bulk HSQ layer, chemical and structural changes at the insulator-metal (HSQ-Mo) interface under applied bias could also contribute to the switching mechanism. We are planning further work to investigate interfacial changes such as proton exchange [17], [18] and the formation of molybdenum oxide [19], [20] at the interface in order to gain a deeper understanding of the switching mechanisms in our devices.…”
Section: Hsq Thin Film Rram Devicesmentioning
confidence: 99%